2009
DOI: 10.1111/j.1749-6632.2009.04815.x
|View full text |Cite
|
Sign up to set email alerts
|

Statins for the Treatment of Antiphospholipid Syndrome?

Abstract: Fluvastatin has been shown to revert proinflammatory/prothrombotic effects of antiphospholipid antibodies (aPL) in vitro and in mice. Here, we examined whether fluvastatin affects the levels of proinflammatory/prothrombotic markers in antiphospholipid syndrome (APS) patients. Vascular endothelial growth factor (VEGF), soluble tissue factor (sTF), tumor necrosis factor-alpha (TNF-alpha), soluble intercellular adhesion molecule-1 (sICAM-1), sE-selectin (E-sel), C-reactive protein (CRP), and soluble vascular cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 70 publications
1
20
0
1
Order By: Relevance
“…Moreover, that research group later demonstrated (by using a murine model of recurrent spontaneous miscarriages that shares features with human recurrent miscarriage and fetal growth restriction) that by inhibiting TF with pravastatin, release of antiangiogenic factor sFlt-1 is inhibited, trophoblast proliferation and placental flow are restored, placental oxidative damage is prevented, and pregnancies are rescued [81]. A recent study by Jajoria et al [82] showed a significant decrease in the titers of VEGF in the plasma of APS patients after 30 days of treatment with fluvastatin. Moreover, that study further addressed the beneficial effects of fluvastatin in other prothrombotic/proinflammatory markers induced by aPLs in APS patients, including TF and TNFα.…”
Section: Statinsmentioning
confidence: 98%
“…Moreover, that research group later demonstrated (by using a murine model of recurrent spontaneous miscarriages that shares features with human recurrent miscarriage and fetal growth restriction) that by inhibiting TF with pravastatin, release of antiangiogenic factor sFlt-1 is inhibited, trophoblast proliferation and placental flow are restored, placental oxidative damage is prevented, and pregnancies are rescued [81]. A recent study by Jajoria et al [82] showed a significant decrease in the titers of VEGF in the plasma of APS patients after 30 days of treatment with fluvastatin. Moreover, that study further addressed the beneficial effects of fluvastatin in other prothrombotic/proinflammatory markers induced by aPLs in APS patients, including TF and TNFα.…”
Section: Statinsmentioning
confidence: 98%
“…Además en 9 pacientes con SAF se midió lo mismo el día de inicio de fluvastatina y a los 30 días de uso (40 mg al día). TNFα, FT y VEGF estaban elevados en los pacientes con SAF, y fluvastatina redujo significativamente estos marcadores en la mayoría de los pacientes que fueron tratados 11 . De manera similar un estudio con 42 pacientes con SAF y 35 sujetos sanos tratados con fluvastatina 20 mg al día por 1 mes mostró reducción significativa de la expresión de FT y VEGF en monocitos, lo que se relacionó con la disminución de la fosforilación de p38 MAPK y de la unión de NFκB al DNA 12 .…”
Section: Estatinasunclassified
“…Many researchers have provided evidence that upregulated TF mRNA and antigen expression and TF pathway activation plays a key role in APS thrombotic manifestations. Indeed, our group found in an ongoing clinical trial, that mean serum levels of soluble TF, tumor necrosis factor- (TNF) and VEGF were significantly elevated in APS patients compared to controls and treatment with fluvastatin, a statin with efficacy in treating APS, resulted in significant decreases of these pro-inflammatory markers in most APS patients [124].…”
Section: Direct Proinflammatory and Prothrombotic Effects Of Antiphosmentioning
confidence: 99%